The Paradigm of Knowledge Integration: The Concept of Fiqh Al-Syāmil Fī Al-Dīn Wa Al-Ḥayāh in The Development of Integral and Holistic Knowledge - Rusman Nurdiansyah; Supiana; Sofwan Gozali; Raka Akhmad Himan Nurwahyu; Nurjaman Wahyu Ramdani (Journal of Research and Thought on Islamic Education (JRTIE), 2026)
The paradigm of Fiqh al-Syâmil fî ad-Dîn wa al-Hayâh represents an epistemological framework that emphasizes the unity of religion and life, revelation and reason, as well as spiritual values and scientific rationality. Within this perspective, knowledge is not value-free but serves as a divine instrument for achieving human and civilizational well-being. This study aims to explore the philosophical meaning of Fiqh al-Syâmil and its implications for the integration of knowledge in Islam, by tracing the thoughts of both classical and contemporary Muslim scholars. Employing a qualitative library research design through Islamic epistemology and philosophy of science approaches, the study analyzes key works by Ismail Raji al-Faruqi, Syed Muhammad Naquib al-Attas, Fazlur Rahman, Kuntowijoyo, Mulyadhi Kartanegara, Amin Abdullah, Harun Nasution, Nanat Fatah Nasir, and Azyumardi Azra. The findings reveal that Fiqh al-Syâmil is grounded in the principle of tawhid as the core of Islamic epistemology, integrating three modes of knowing: bayani (textual-revelatory), burhani (rational-empirical), and ‘irfani (spiritual-intuitive). The synthesis of these dimensions results in an integral, ethical, and civilizational model of knowledge capable of bridging the gap between religious and secular sciences. Conceptually, this paradigm aligns with al-Faruqi’s Islamization of Knowledge, al-Attas’s adab-based epistemology, Kuntowijoyo’s prophetic social science, and Amin Abdullah’s interconnected integration. Within Islamic higher education, Fiqh al-Syâmil serves as a foundational framework for developing integrative curricula, interdisciplinary research, and epistemological reconstruction oriented toward human welfare and moral civilization.